2013
DOI: 10.1007/s00296-013-2743-y
|View full text |Cite
|
Sign up to set email alerts
|

TNF inhibitors induce discoid fibrosis in the sublining layers of the synovium with degeneration of synoviocytes in rheumatoid arthritis

Abstract: We determined the characteristic features of synovial tissues of rheumatoid arthritis (RA) patients treated by TNF inhibitors in order to delineate their mechanism of action. Synovial tissues were obtained during the joint surgical operations from 12 RA patients who had been treated with TNF inhibitors in addition to disease modifying antirheumatic drugs (DMARDs) for at least 5 months (5–25 months) (RA-TNFinh), and from 12 RA patients who had been treated with DMARDs alone (RA-DMARD), and were evaluated under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The explanation for those differences between our cohort and other studies could be the occurrence of biological drugs in the treatment of RA in the 2000s, which could have resulted in modifications of synovial inflammatory infiltrate in more recent tissue specimen from treated patients as the ones in this study. In support of this hypothesis, Hirohata et al have demonstrated that TNF inhibitors alter the histological characteristics of the synovium from RA patients [21]. Another result of our study is the absence of difference in synovial architecture between RA and OA patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The explanation for those differences between our cohort and other studies could be the occurrence of biological drugs in the treatment of RA in the 2000s, which could have resulted in modifications of synovial inflammatory infiltrate in more recent tissue specimen from treated patients as the ones in this study. In support of this hypothesis, Hirohata et al have demonstrated that TNF inhibitors alter the histological characteristics of the synovium from RA patients [21]. Another result of our study is the absence of difference in synovial architecture between RA and OA patients.…”
Section: Discussionsupporting
confidence: 88%
“…This study reinforces our knowledge upon the specificity of synovial architecture and cell distribution of inflammatory infiltrate in synovium of patients with RA. Therefore in RA, a systematic histological analysis of synovial biopsy could be interesting for early diagnosis, to establish a prognosis and for treated patient's follow-up [21,37,38]. Indeed, even if a synovial biopsy guided by echography or arthroscopy is an invasive act, it can provide synovial tissue specimen of good quality from the most representative lesions of the joint [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, TNF inhibitors have been shown to have high efficacy against RA in humans by suppressing TNF-α and inducing cell death in FLSs (45). SL fibrosis has been reported to occur when TNF inhibitors are used in RA therapy (12). Although TNF inhibitor therapy can be expected to prevent cell accumulation, it might only marginally affect pre-existing cell accumulation (46).…”
Section: Discussionmentioning
confidence: 99%
“…At present, one of the most effective drugs are tumor necrosis factor (TNF) inhibitors, the therapeutic mechanism of which is reported to be suppressing inflammation by reducing FLS influx into the LL (9). Nonetheless, TNF inhibitor therapy has little effect on FLSs in the SL (9) and has even been reported to cause fibrosis of the SL (12). Therefore, improving SL-FLS accumulation is thought to be difficult with existing therapies (13).…”
Section: Introductionmentioning
confidence: 99%